FISCAL OVERVIEW OF SPORTS PUBLIC SPENDING IN EDUCATION - Vaca Medina, Gustavo (Revista Inclusiones, 2021)
Mexico, as a member of the Organization for Economic Cooperation and Development (OECD), has shown in recent years that its level in education is below the average that other member countries have. Given this, the relationship between public spending directed to sport and the impact it generates on the educational indicators of the State of Jalisco will be determined. It is used a subset of 39 municipalities analyzed by means of a model with panel data through estimates with fixed effects. There is no evidence of positive effects of the expenditure allocated to sport on education indicators and, consequently, there is no improvement in school performance. The conclusion is that the tools of action used by the State do not comply with a principle of coherence, since they understand that the problems must be solved with instruments aligned with their nature.